THE BENEFITS OF KPI TO ENHANCE EMPLOYEES IN MANUFACTURING COMPANIES - G.Zufarova,B.Mukhtarova (International Journal of Literature and Language Studies, 2026)
Currently, in the conditions of economic reforms being carried out in our country, it is important for production enterprises not only to effectively use economic, financial and material resources, but also to attract labor resources to work in a reasonable way. Personnel management is a broad concept, which includes the selection of employees, their retention, professional retraining, creating opportunities and necessary conditions for improving their knowledge and skills, correctly and objectively evaluating their activity in the enterprise and increasing their efficiency.